Anaesthetic efficacy of lidocaine/clonidine for inferior alveolar nerve block in patients with irreversible pulpitis. (10th June 2016) - Shadmehr, E.; Aminozarbian, M. G.; Akhavan, A.; Mahdavian, P.; Davoudi, A.
Abstract: Aims: This prospective, randomized, double‐blind study aimed to compare the efficacy of lidocaine with epinephrine versus lidocaine with clonidine for inferior alveolar nerve block (IANB) and hemodynamic stability (heart rate, systolic blood pressure, diastolic blood pressure and mean arterial pressure) in patients with irreversible pulpitis. Methodology: One hundred patients with irreversible pulpitis in mandibular molar teeth randomly received 1.8 mL of 2% lidocaine with clonidine (15 μg mL −1 ) or 1.8 mL of 2% lidocaine with epinephrine (12.5 μg mL −1 ), using a conventional IANB technique. Endodontic access cavities were prepared 15 min after solution deposition, and all patients were required to have profound lip numbness. Success was defined as no or mild pain (visual analog scale recording) upon endodontic access cavity preparation or initial canal instrumentation. The hemodynamic parameters were measured before, during and 5, 10 and 30 min after administration. Finally, the collected data were subjected to independent t ‐test, chi‐square and Fisher's exact test usingspss software ver.20 at a significant level of 0.05. Results: The success rates for IANB using lidocaine with epinephrine and lidocaine with clonidine solutions were 29% and 59%, respectively. The clonidine group exhibited a significantly higher success rate ( P < 0.05). Five minutes after drug administration, systolic blood pressure and heart rate significantly increased in the lidocaine with epinephrine group and insignificantly decreased in lidocaine with clonidine group. Conclusion: For mandibular molars with irreversible pulpitis, addition of clonidine to lidocaine improved the success rate of IANB compared to a standard lidocaine/epinephrine solution.